2021
DOI: 10.1002/hyp.14200
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors regulating stream nitrate concentrations at baseflow condition in a large region encompassing a climatic gradient

Abstract: Though high rates of nitrate (NO 3 À ) leaching from forests are undesirable, the factors significantly regulating stream NO 3 À concentration is not clarified yet. In Japan, not only near metropolitan areas but also the Japan Sea-side area with heavy snowfall is well known for receiving more than 10 kg-N ha À1 year À1 of nitrogen (N) deposition.However, NO 3 À concentration in stream water is relatively low in the Japan Sea-side area compared with its concentration in other areas. We examined important enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 72 publications
2
20
1
Order By: Relevance
“…The averaged N deposition in the Japan-sea side in the KIN (hereafter, the JSK) was larger than the one in the entire KIN though both were relatively large as described below in the "Study area and database development" section. However, the stream NO 3 − concentrations in JSK were lower than the entire KIN [13,14]. Though all possible factors which can affect NO 3 − leaching such as topography [15,16], climate [8,[17][18][19][20][21], vegetation [9,22,23], soil chemistry [9,22,23], soil type [24,25], geology [26][27][28], and historical land-use and disturbance [8,9,[29][30][31] were examined, Makino et al [14] demonstrated that both the amount of N deposition and several climatic factors such as precipitation and temperature were important for regulating stream NO 3 − concentrations at baseflow conditions.…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…The averaged N deposition in the Japan-sea side in the KIN (hereafter, the JSK) was larger than the one in the entire KIN though both were relatively large as described below in the "Study area and database development" section. However, the stream NO 3 − concentrations in JSK were lower than the entire KIN [13,14]. Though all possible factors which can affect NO 3 − leaching such as topography [15,16], climate [8,[17][18][19][20][21], vegetation [9,22,23], soil chemistry [9,22,23], soil type [24,25], geology [26][27][28], and historical land-use and disturbance [8,9,[29][30][31] were examined, Makino et al [14] demonstrated that both the amount of N deposition and several climatic factors such as precipitation and temperature were important for regulating stream NO 3 − concentrations at baseflow conditions.…”
Section: Introductionmentioning
confidence: 88%
“…In a previous study, the key factors regulating NO 3 − leaching from watersheds without human-created features were identified across the Kinki region (KIN), a large region (28,914 km 2 ) of Japan, using random forest (RF) regression, a machine learning technique [14]. The KIN includes a portion of the Japan-sea side and experiences considerable variation in N deposition and climatic conditions.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations